2000
DOI: 10.1093/nar/28.15.2935
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of a cognate RNA aptamer by neomycin B: quantitative evaluation of hydrogen bonding and electrostatic interactions

Abstract: Aminoglycosides are an important class of antibiotic that selectively target RNA structural motifs. Recently we have demonstrated copper derivatives of amino-glycosides to be efficient cleavage agents for cognate RNA motifs. To fully develop their potential as pharmaceutical agents it is necessary to understand both the structural mechanisms used by aminoglycosides to target RNA, and the relative contributions of hydrogen bonding and electrostatic interactions to recognition selectivity. Herein we report resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 27 publications
8
63
0
Order By: Relevance
“…RNA aptamers that specifically bound to neomycin-B over paromomycin were identified by in vitro selection (Wallis et al 1995) and this aptamer-ligand interaction has been studied intensively (Wallis and Schroeder 1997;Cowan et al 2000;de-los-Santos-Alvarez et al 2007Stampfl et al 2007). With the intent to use NEO1A in synthetic biology applications that would require that the aptamer be functional in the cell cytoplasm, we examined the interaction of NEO1A with its ligands in Buffer A that emulates the free ion concentrations of the mammalian cell cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA aptamers that specifically bound to neomycin-B over paromomycin were identified by in vitro selection (Wallis et al 1995) and this aptamer-ligand interaction has been studied intensively (Wallis and Schroeder 1997;Cowan et al 2000;de-los-Santos-Alvarez et al 2007Stampfl et al 2007). With the intent to use NEO1A in synthetic biology applications that would require that the aptamer be functional in the cell cytoplasm, we examined the interaction of NEO1A with its ligands in Buffer A that emulates the free ion concentrations of the mammalian cell cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…The complex is stabilized by electrostatic and Hbonding interactions (Wallis and Schroeder 1997;Cowan et al 2000;de-los-Santos-Alvarez et al 2007Stampfl et al 2007). Our NMR results (performed in a similar buffer as the original study) are consistent with the reported structure of the neomycin-B-NEO1A complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang & Rando, 1995) Tobramycin 2'-OMe-RNA Electrochemical (Impedence) 0.7 µM (González-Fernández et al, 2011) RNA 180 -- (Kwon et al, 2001) Kanamycin RNA 10-30 -- (Goertz, Colin Cox Ellington, 2004b) RNA Low nM -- (Goertz, Colin Cox Ellington, 2004b) RNA 1800 -- (Cowan et al, 2000) Electrochemical (Impedence) "sub µM" (de-los-Santos-Alvarez et al, 2007) Neomycin 2'-OMe-RNA Surface Plasmon Resonance (SPR) 10 nM (de-los-Santos-Álvarez et al, 2009) - (Cruz-Aguado & Penner, 2008a) Fluorescence Polarization 5 nM (Cruz-Aguado & Penner, 2008b) Electrochemical 30 pg/mL (Kuang et al, 2010) Electrochemiluminescent 0.007 ng/mL (Z. Wang et al, 2010) Mycotoxins Ochratoxin A DNA 200…”
Section: Aminoglycosidesmentioning
confidence: 99%
“…Aptamers are particularly attractive as therapeutics since they are not immunogenic, can be chemically synthesized and are amenable to chemical modifications (Kusser 2000). Target-specific aptamers are created through SELEX Piasecki et al 2009) against many types of targets, ranging from small organic molecules like neomycin (Cowan et al 2000), viral peptides like HIV-1 Rev (Ye et al 1999), to large macromolecules such as thrombin (Macaya et al 1993). Of the hundred odd aptamer structures that have been deposited into the PDB, only six are protein-RNA aptamer complexes, 2 and only three of these represent proteins that do not natively bind nucleic acids.…”
Section: Introductionmentioning
confidence: 99%